Safeguarding Civilian Internet Access During Armed Conflict: Protecting Humanity’s Most Important Resource in War - Hutchins, Todd Emerson (Science and Technology Law Review, 2021)
A recent spate of governmental shutdowns of the civilian internet in a broad range of violent contexts, from uprisings in Hong Kong and Iraq to armed conflicts in Ethiopia, Kashmir, Myanmar, and Yemen, suggests civilian internet blackouts are the ‘new normal.’ Given the vital and expanding role of internet connectivity in modern society, and the emergence of artificial intelligence, internet shutdowns raise important questions regarding their legality under intentional law. This article considers whether the existing international humanitarian law provides adequate protection for civilian internet connectivity and infrastructure during armed conflicts. Concluding that current safeguards are insufficient, this article proposes a new legal paradigm with special protections for physical internet infrastructure and the right of civilian access, while advocating the adoption of emblems (such as the Red Cross or Blue Shield) in the digital world to protect vital humanitarian communications.